2007
DOI: 10.1177/0961203307081895
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of the novel cytokine HMGB1 to the cytoplasm and extracellular space coincides with the peak of clinical activity in experimentally UV-induced lesions of cutaneous lupus erythematosus

Abstract: HMGB1 is a pro-inflammatory cytokine that together with TNF-alpha and IL-1beta is involved in the pathogenesis of spontaneously occurring skin lesions in lupus erythematosus. The purpose of the present study was to explore the sequence of events in HMGB1, TNF-alpha and IL-1beta expression under development and resolution of experimentally induced CLE lesions. The study involved investigation of 38 serial skin biopsies acquired from photoprovoked skin lesions of nine CLE patients, using immunohistochemical stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 33 publications
4
59
1
3
Order By: Relevance
“…HMGB1 is secreted actively by immune cells such as monocytes, macrophages, and dendritic cells [6]. A previous study suggested that the cytoplasmic HMGB1 existed in lesional skin of lupus erythematosus, psoriasis vulgaris and AD [26,27]. In our study, we also found that HMGB1 expression was up regulated in AD mice and treatment with resveratrol attenuated this process (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…HMGB1 is secreted actively by immune cells such as monocytes, macrophages, and dendritic cells [6]. A previous study suggested that the cytoplasmic HMGB1 existed in lesional skin of lupus erythematosus, psoriasis vulgaris and AD [26,27]. In our study, we also found that HMGB1 expression was up regulated in AD mice and treatment with resveratrol attenuated this process (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Within the lesional skin of cutaneous lupus, increased amounts of cytoplasmic and extracellular HMGB1 were detected together with high expression of TNFa and IL-1b [63]. A follow up investigation revealed cytoplasmic and extracellular HMGB1 at the peak of clinical activity in experimentally ultraviolet light (UV)-induced lesions of cutaneus lupus [64].…”
Section: Biological Effects Of Hmgb1mentioning
confidence: 97%
“…High mobility group box 1 (HMGB1) protein is a nuclear protein that was identified as a potent pro-inflammatory mediator that can translocate from the nucleus to the cytoplasm and extracellular space [12]. HMGB1 can be passively released by necrotic or damaged cells [13] and can be detected in serum samples as a biomarker [14,15].…”
Section: Introductionmentioning
confidence: 99%